Unpacking Journalists' (Dis)Trust: Expressions of Suspicion in the Narratives of Journalists Covering the Israeli-Palestinian Conflict. (October 2019) - Aharoni, Tali; Tenenboim-Weinblatt, Keren
Despite growing attention to notions of (dis)trust in both journalism studies and conflict studies, the role of suspicion and distrust in the dynamics of conflict coverage has not yet been investigated. This paper explores the various aspects of suspicion in the perceptions of journalists covering the Israeli-Palestinian conflict, drawing on twenty in-depth interviews with journalists and an interdisciplinary approach to the conceptualization of suspicion and (dis)trust. An inductive-qualitative analysis of journalists' narratives identified three main aspects: suspicion of information sources, suspicion of peer journalists, and awareness of being under suspicion. The study demonstrates that through all stages of news production, journalists operate within a perpetual context of suspicion despite being required to generate trust. This dilemma culminates in hostile environments, where journalists must trust their sources in order to ensure their physical security yet are professionally required to epistemically suspect the information delivered by these same sources. Taken together, the manifestations of suspicion identified in this study provide an analytical framework for understanding (dis)trust within journalism and for further studying the processes through which these manifestations can contribute to public trust in both the media and conflict parties.